Anemia Prevention in Adolescent Females With Lawrence W. Green Theory Approach: Literature Review - Mujiono Ismail; Siti Aisah; Edy Soesanto; Satriya Pranata (Babali Nursing Research)
This literature review is based on the fact that anemia is one of the health problems throughout the world, especially in developing countries, the prevalence of anemia in the world is very high, especially in developing countries including Indonesia. Adolescent girls are susceptible to anemia, the menstrual cycle every month is one of the factors that causes adolescent girls to be susceptible to anemia. The method employed in writing this article is a literature review of articles published in 2020-2024 through two sources, namely Google Scholar, PuPMed and Science Direct with the keywords "Anemia", "Prevention", "Adolescent girls", "Lawrence W. Green's Theory". After going through the screening process, of the 883 articles found, 15 articles that have been reviewed, the results show that each individual has their own behavior that is different from other individuals, including identical twins. Behavior does not always follow a certain order so that the formation of positive behavior is not always influenced by knowledge and positive attitudes where according to Lawrence W. Green's Theory which classifies several factors that cause an action or behavior, namely 1) Predisposing factors, 2) Enabling factors, 3) Reinforcing factors. The preventing factors for anemia in adolescent girls are influenced by the level of knowledge, attitudes, peer support, and health facilities.